Environmental tobacco smoke and the risk of cardiovascular disease - Jousilahti, Pekka; Patja, Kristiina; Salomaa, Veikko (Scandinavian Journal of Work, Environment & Health, 2002)
Disease risk due to smoking is not limited to smokers only. Passive smoking, exposure to environmental tobacco smoke, is associated with adverse health effects, and it increases the risk of several diseases. This paper summarizes the cardiovascular effects of tobacco smoke and the current data on the effects of environmental tobacco smoke on the development of cardiovascular disease. According to the results of epidemiologic and experimental studies, environmental tobacco smoke has marked harmful effects on the cardiovascular system. It is estimated that it increases the risk of an acute event of coronary heart disease by 25–35%. Even though the number of studies conducted in the work environment is small, there is no reason to assume that the cardiovascular effects of environmental tobacco smoke differ markedly between the home and the workplace. Firm and timely actions are needed to protect people from exposure to environmental tobacco smoke, both in occupational and other environments.
Keywords: cardiovascular disease; coronary heart disease; disease; environmental tobacco smoke; epidemiology; experimental study; overview; passive smoking; risk